THE EFFECT OF ADDITION OF ROSELA EXTRACT IN POVERTY REBON SHRIMP POWDER (Aceteserythraeus) ON CONSUMER RECEIPT - Khoirotun Asma; Suparmi Suparmi; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The effect of the addition of roselle extract on the shrimp paste of shrimp rebon (aceteserythraeus) to consumer acceptance has been done in july-july 2017. This study aims to find out the effect of the addition of roselle extract with different concentration on shrimp paste shrimp powder to consumer acceptance. The method used in this study is the experimental method that is conducting experiments making terasi with the addition of roselle extract with different concentrations. The experimental design used was Completely Randomized Design (RAL) of one factor with three treatment levels, ie without addition of roselle extract 0% (R1), addition of 10% roselle extract (R2) and addition of roselle extract 20% (R3). The experiment was repeated 3 times, so the number of experimental units in the study was 9 units. Based on the level of consumer acceptance, the best treatment is the best treatment of organoleptic treatment in R3 treatment with the average value of rupa (2,955), the aroma with the average value (2,817), and the texture with the average value (2,750) . While the best proximate result was found in R3 with protein content with value (20,745%), water content (9,8933%), and ash content with value (2,8933%).Keywords:Rebon Shrimp,Rosela Flower,Terasi Powder